2003
DOI: 10.1002/prot.10235
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio construction of polypeptide fragments: Accuracy of loop decoy discrimination by an all‐atom statistical potential and the AMBER force field with the Generalized Born solvation model

Abstract: We describe a novel method to generate ensembles of conformations of the main-chain atoms {N, C␣, C, O, C␤} for a sequence of amino acids within the context of a fixed protein framework. Each conformation satisfies fundamental stereochemical restraints such as idealized geometry, favorable / angles, and excluded volume. The ensembles include conformations both near and far from the native structure. Algorithms for effective conformational sampling and constant time overlap detection permit the generation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
154
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 87 publications
8
154
1
Order By: Relevance
“…This finding suggests that the use of statistical database potentials, as opposed to realistic models based on physical chemical principles, has a fundamental limitation in achieving high-resolution structural refinement. Other published results using such potentials to carry out loop predictions led to similar conclusions; in particular, the recent results of de Bakker et al 23 have also suggested that all-atom force fields are capable of qualitative improvements in accuracy relative to statistical potentials. It is difficult to see how the fine details of flexible loop structure can be captured by a potential function that in essence ignores solvation effects and electrostatics and incorporates conformational analysis only at a very approximate level.…”
Section: Accuracy Of Loop Predictionsupporting
confidence: 59%
See 2 more Smart Citations
“…This finding suggests that the use of statistical database potentials, as opposed to realistic models based on physical chemical principles, has a fundamental limitation in achieving high-resolution structural refinement. Other published results using such potentials to carry out loop predictions led to similar conclusions; in particular, the recent results of de Bakker et al 23 have also suggested that all-atom force fields are capable of qualitative improvements in accuracy relative to statistical potentials. It is difficult to see how the fine details of flexible loop structure can be captured by a potential function that in essence ignores solvation effects and electrostatics and incorporates conformational analysis only at a very approximate level.…”
Section: Accuracy Of Loop Predictionsupporting
confidence: 59%
“…Some studies have used purely gas-phase energetics, 18 whereas the early study of Moult and James 6 used an image-charge method to represent charge screening, and several studies have used simple distance-dependent dielectric models. 13 23 used a similar energy function on a large database of loop decoys. The energy function used here is similar (OPLS all-atom force field 24 -26 and Surface Generalized Born model of solvation 27,28 ), but the sampling algorithms used are entirely new and make it possible to apply a realistic, well-validated solvent model to a large test set of loops, with modest computational expense.…”
Section: Overview Of Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, de novo/ab initio predictions for loop regions shorter than 12 residues tend to be reliable (113 , 114 ), if constructed using reasonable physicalchemical force fields that incorporate descriptions of the aqueous solution rather than a vacuum environment (115 , 116 ). Existing loop-prediction programs include Loopy (117), RAPPER (114) and PLOP (113) (Table 5); of these, PLOP is reportedly the most accurate, although it requires the most computational time, whereas Loopy is the fastest. Other strategies have been reported for loop modeling in GPCRs, including simulated annealing with Monte Carlo (116) and coarse-grained backbone dihedral sampling (118), although larger benchmarks are required to confirm their general applicability.…”
Section: D-structure Predictionmentioning
confidence: 99%
“…Alignments were obtained using FUGUE (19). The MAb models were built using MODELLER (30) and RAPPER (31,32) and validated with PROCHECK (25) and VERIFY3D (26). HBPLUS was used for hydrogen bond definition (33).…”
Section: Modelling Of 21-oh and 21-oh Mabsmentioning
confidence: 99%